Pengaruh Atribut Produk Terhadap Loyalitas Konsumen : Studi Pada Pengguna Lampu Philips di Kota Ambon - Nanulaitta, Deflin Tresye; Sapulette, Ludy (Fakultas Ekonomi Universitas Wisnuwardhana, 2014)
This study aims to examine and analyze the effect of productattributes on consumer loyalty Philips light users in the city of Ambon. Thecollection of the data used in this study is a questionnaire survey with a LikertScale and literature study. Samples using probability sampling by conveniencesampling technique as many as 100 people. While the analysis method used isdescriptive analysis and multiple regression analysis. The results showed that thevariable attribute indicates Philips lighting products significantly influencecustomer loyalty in the city of Ambon. Based on the results of coefficient ofdetermination can be explained that the variable product attributes Philips lamp at100% influence on consumer loyalty in the city of Ambon.Keywords: product atribute, customer loyalty